An exploratory paper on civil society in Jiu Valley. The case of coalition ”Valea Jiului implicată” - Beserman, Edi Dragoș (Journal of Community Positive Practices, 2023)
Up to this date very few empirical studies that address the civil society sector in Jiu Valley have been conducted. If they touch upon this topic, they discuss only the associational life of the miners. However, this does constitute their main objective. Thus, civil society actors beyond the miners’ unions are neglected. Recognizing the scarcity of research on this topic, the paper seeks to address this gap, by taking the case of the coalition of Valea Jiului Implicată/Jiu Valley Involved. In order to find out more about this coalition and its members, I used a mixed method approach consisting of both quantitative and qualitative methods. Results show that the coalition was formed by educated individuals with an experience of migration, that managed to bring together volunteers and NGOs so that they can address different problems affecting the region.